The impact of physical education on students' active lifestyles - Widiyatmoko, Fajar Ari; Pradipta, Galih Dwi; Hudah, Maftukin (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2020)
The curriculum in Indonesia tends to change and has not been able to contribute significantly to changes in the learning process, especially in the active lifestyle of students. The purpose of this study is to determine the effect of Physical Education learning on active lifestyles. The design of this study is ex-post facto. The study involved high school students in Central Java in 2019. The data about Physical Education was collected by using a questionnaire to measure self-perception, motivation, and PACES (enjoyment), while the physical activity variable was measured by IPAQ (International Physical Activity Questionnaire). The results of the study indicated that the level of physical activity of students was moderate. Physical education variables as a whole were significantly related. In gender, in women, the motivational factor did not affect the level of physical activity. Whereas in men all factors in the context of physical education were not related to the level of physical activity. The conclusion of this study is physical education affects the active lifestyle of students. Factors outside physical education are more dominant in influencing male students in carrying out their physical activities. Physical education teachers must translate the curriculum into classroom learning by designing models and methods that are in accordance with the conditions of students and school facilities so that Physical Education has more impact on students' physical competences.